2021
DOI: 10.5755/j01.erem.77.4.25043
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Littering through Improved Visual Design

Abstract: Littering is a daunting environmental issue that occurs daily; the impact of littering can range from lowering the aesthetic appeal of a city to polluting waterways and biomes. Littering persists on a collective and individual level despite the existence of numerous laws and regulations that prohibit it. We assume that there is a correlation between the effectiveness of visual aids and littering behavior. Poorly designed prohibitive signs and inaccessible trash bins could be part of the reason why littering pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Research has shown that including a brief explanation as to why a behaviour is prohibited and the addition of 'watching eyes' images can increase the efficacy of signage but will not completely eliminate the antisocial behaviour [15] and may increase the incidence of other 'displacement' behaviours which may also be antisocial [16]. The presence of litter bins has been shown to decrease littering; however, the design and positioning of the litter bin as well as associated signage may have a significant impact on their use [17,18]. Review of current signage and litter bins may aid in decreasing incidences of littering within the collection.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that including a brief explanation as to why a behaviour is prohibited and the addition of 'watching eyes' images can increase the efficacy of signage but will not completely eliminate the antisocial behaviour [15] and may increase the incidence of other 'displacement' behaviours which may also be antisocial [16]. The presence of litter bins has been shown to decrease littering; however, the design and positioning of the litter bin as well as associated signage may have a significant impact on their use [17,18]. Review of current signage and litter bins may aid in decreasing incidences of littering within the collection.…”
Section: Discussionmentioning
confidence: 99%
“…Other understudied components that are linked to the presentation and exchange of information were highlighted. Indeed, specific urban components within the 'Structural/Infrastructure' category that relate to signage were only investigated once in the reviewed articles, such as information boards (Budner, 2016), posters (Johannes et al, 2021), signboards (Wang et al, 2010), and other wayfinding objects (Hunter & Askarinejad, 2015). Similar to art, signage, and other textual elements have been regarded as 'urban aesthetic' objects and should also be researched more within this context (Chana et al, 2023;see Kim &Mitschke et al, 2017 from the reviewed articles).…”
Section: Urban Componentsmentioning
confidence: 99%
“…If children see their parents throwing trash into the river, there is a significant likelihood that the children will follow in their parent's footsteps and do the same [12]. The negative effects of littering can range from lessening a city's appeal from an aesthetic standpoint to polluting waterways and ecosystems [13].…”
Section: Fig 3 Existing Condition Of Wastewater Managementmentioning
confidence: 99%